Protective Effect of Remdesivir Against Pulmonary Fibrosis in Mice - Li, Xiaohe; Liu, Rui; Cui, Yunyao; Liang, Jingjing; Bi, Zhun; Li, Shimeng; Miao, Yang; Zhang, Liang; Li, Xiaoping; Zhou, Honggang; Yang, Cheng (Frontiers in Pharmacology, 2021)
Pulmonary fibrosis is a known sequela of severe or persistent lung damage. Existing clinical, imaging and autopsy studies have shown that the lungs exhibit a pathological pulmonary fibrosis phenotype after infection with coronaviruses, including severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Pulmonary fibrosis may be one of the most serious sequelae associated with coronavirus disease 2019 (COVID-19). In this study, we aimed to examine the effects of the antiviral drug remdesivir on pulmonary fibrosis. We used a mouse model of bleomycin-induced pulmonary fibrosis to evaluate the effects of remdesivir on pulmonary fibrosis in vivo and further explored the potential pharmacological mechanisms of remdesivir in lung fibroblasts and alveolar epithelial cells in vitro. The in vivo experiments showed that remdesivir significantly alleviated bleomycin-induced collagen deposition and improved pulmonary function. In vitro experiments showed that remdesivir dose-dependently suppressed TGF-β1-induced lung fibroblast activation and improved TGF-β1-induced alveolar epithelial injury. Our results indicate that remdesivir can alleviate the severity of pulmonary fibrosis and provide some reference for the prevention and treatment of pulmonary fibrosis in patients with COVID-19.